Time course of biomechanics during jump landing before and after two different fatigue tasks - Makoto Asaeda; Kazuhiko Hirata; Tomoya Ohnishi; Hideyuki Ito; So Miyahara; Koki Fukuhara; Yuki Nakashima; Yoshitaka Iwamoto; Kai Ushio; Yukio Mikami; Nobuo Adachi (Elsevier, 2024)
Objective: Muscle fatigue contributes to anterior cruciate ligament (ACL) injuries, with increased knee and hip abduction observed during fatigue. However, there have been no reports revealing the differences between fatigue tasks or the duration of these changes. In this study, we conducted single-leg drop landings before and after hip and knee fatigue tasks to elucidate the changes in lower limb biomechanics over time. Methods: Twenty-two male participants performed single-leg drop landings before, immediately after, and 5, 10, and 15 min after fatigue tasks involving isokinetic hip abduction/adduction (hip fatigue task [HFT]) and knee extension/flexion (knee fatigue task [KFT]). Hip and knee kinematic and kinetic data were collected using a three-dimensional motion analysis device and two force plates. A two-way ANOVA was performed with both the fatigue task (HFT and KFT) and time point (Time 1 to Time 4) as factors, and the main effects and interactions were calculated. Results: The knee adduction angle after the HFT was significantly greater than that after KFT immediately following the fatigue task. The knee flexion moment was significantly lower in the KFT, whereas the knee adduction and internal rotation moments were significantly higher in the HFT immediately after the fatigue task. Conclusion: This study revealed distinct kinematic and kinetic changes specific to each fatigue task, particularly in the frontal plane for hip joint tasks and the sagittal plane for knee joint tasks. These findings could assist in the development of ACL injury prevention programs tailored to the functional improvement and exercise capacity of each joint.